Epistemological beliefs and their impact on work, subjectivity and learning - Harteis, Christian; Gruber, Hans; Lehner, Franz (Work, subjectivity and learning)

Oser, F. & Spychiger, M.(2005). Lernen ist schmerzhaft. Zur Theorie des Negativen Wissens und zur Praxis der Fehlerkultur - Harteis, Christian (SCHWEIZERISCHE ZEITSCHRIFT FUR BILDUNGSWISSENSCHAFTEN)

How to close the value gap between market and tax values - Mueller, Jens (EcoMod 2006)

Randomness and Secrecy - A Brief Introduction - Blömer, Johannes (Journal of Universal Computer Science (J.UCS))
We give a brief introduction to probabilistic encryptions. This serves as an example how randomness plays a pivotal role in cryptographic systems that satisfy advanced security concepts.

Fault Based Collision Attacks on AES - Blömer, Johannes; Krummel, Volker (Lecture Notes in Computer Science)

Wagner’s Attack on a Secure CRT-RSA Algorithm Reconsidered - Blömer, Johannes; Otto, Martin (Lecture Notes in Computer Science)

Sign Change Fault Attacks on Elliptic Curve Cryptosystems - Blömer, Johannes; Otto, Martin; Seifert, Jean-Pierre (Lecture Notes in Computer Science)

Influence of adaptive data layouts on performance in dynamically changing storage environments - Brinkmann, Andre; Effert, Sascha; Heidebuer, Michael; Vodisek, Mario (14th Euromicro International Conference on Parallel, Distributed, and Network-Based Processing (PDP'06))
For most of today's IT environments, the tremendous need for storage capacity in combination with a required minimum I/O performance has become highly critical. In dynamically growing environments, a storage management solution's underlying data distribution scheme has great impact to the overall system I/O performance. The evaluation of a number of open system storage visualization solutions and volume managers has shown that all of them lack the ability to automatically adapt to changing access patterns and storage infrastructures; many of them require an error prone manual re-layout of the data blocks, or rely on a very time consuming re-striping of all available data. This paper evaluates the performance of conventional data distribution approaches compared to the adaptive virtualization solution V:DRIVE in dynamically changing storage environments. Changes of the storage infrastructure are normally not considered in benchmark results, but can have a significant impact on storage performance. Using synthetic benchmarks, V:DRIVE is compared in such changing environments with the non-adaptive Linux logical volume manager (LVM). The performance results of our tests clearly outline the necessity of adaptive data distribution schemes.

The influence of habitual protein intake in early childhood on BMI and age at adiposity rebound: results from the DONALD Study - Günther, A L B; Buyken, Anette; Kroke, A (International Journal of Obesity)

REVIS – Reform der Ernährungs- und Verbraucherbildung in Schulen - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Zur Analyse von Unterrichtsmaterialien für die Ernährungs- und Verbraucherbildung - Methfessel, B.; Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Gesundheits- und Innovationsmanagement

Pattern-based Reengineering of Software Systems - Meyer, Matthias (Proceedings of the 13th Working Conference on Reverse Engineering (WCRE 2006), Benevento, Italy)

A Prototype for Guideline Checking and Model Transformation in Matlab/Simulink - Giese, Holger; Meyer, Matthias; Wagner, Robert (Proc. of the 4th International Fujaba Days 2006, Bayreuth, Germany)

On Semantic Issues in Story Diagrams - Tichy, Matthias; Meyer, Matthias; Giese, Holger (Proc. of the 4th International Fujaba Days 2006, Bayreuth, Germany)

Entwicklung von Geschäftsprozessmustern zur Qualitätssicherung - Holtmann, Jörg

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IEEE Trans. Mob. Comput.)

Distributed coloring in O/spl tilde/(/spl radic/(log n)) bit rounds - Kothapalli, Kishore; Scheideler, Christian; Onus, Melih; Schindelhauer, Christian (IPDPS)

Robust Random Number Generation for Peer-to-Peer Systems - Awerbuch, Baruch; Scheideler, Christian (OPODIS)

Towards a scalable and robust DHT - Awerbuch, Baruch; Scheideler, Christian (SPAA)

Mechanical and Hybrid Joining - Meschut, Gerson (Magnesium Technology)

„Wir wollen die Fügeprozesskosten ganzheitlich reduzieren“ - Meschut, Gerson

Mechanisches Fügen höherfester Stähle im Fahrzeugbau - Meschut, Gerson; Timm, M.; Draht, T.

Self-Coordinating Systems: The Next Challenge in Research on Distributed Systems
We present a parallel algorithm for the rendering of complex three-dimensional scenes. The algorithm runs across heterogeneous architectures of PC-clusters consisting of a visualization-node, equipped with a powerful graphics adapter, and cluster nodes requiring weaker graphics capabilities only. The visualization-node renders a mixture of scene objects and simplified meshes (Reliefboards). The cluster nodes assist the visualization-node by asynchronous computing of Reliefboards, which are used to replace and render distant parts of the scene. Our algorithm is capable of gaining significant speedups if the cluster's nodes provide weak graphics adapters only. We trade the number of cluster nodes off the scene objects' image quality.

Foundations of Formal Sciences IV. The History of the Concept of Formal Sciences

New trends in parallel and distributed computing - Monien, Burkhard; Meyer auf der Heide, Friedhelm

Optical switching in metallic photonic crystal slabs with photoaddressable polymers - Nau, D.; Bertram, R.P.; Buse, K.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S.G.; Gippius, N.A.; Giessen, H. (Applied Physics B)

Metallodielectric photonic crystal superlattices: Influence of periodic defects on transmission properties - Zentgraf, Thomas; Christ, A.; Kuhl, J.; Gippius, N. A.; Tikhodeev, S. G.; Nau, D.; Giessen, H. (Physical Review B)

Resonances of split-ring resonator metamaterials in the near infrared - Rockstuhl, C.; Zentgraf, Thomas; Guo, H.; Liu, N.; Etrich, C.; Loa, I.; Syassen, K.; Kuhl, J.; Lederer, F.; Giessen, H. (Applied Physics B)

Disorder issues in metallic photonic crystals - Nau, D.; Schönhardt, A.; Bauer, C.; Christ, A.; Zentgraf, Thomas; Kuhl, J.; Giessen, H. (physica status solidi (b))

Interaction between localized and delocalized surface plasmon polariton modes in a metallic photonic crystal - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Martin, O. J. F.; Kuhl, J.; Giessen, H. (physica status solidi (b))

Controlling the interaction between localized and delocalized surface plasmon modes: Experiment and numerical calculations - Christ, A.; Zentgraf, Thomas; Tikhodeev, S. G.; Gippius, N. A.; Kuhl, J.; Giessen, H. (Physical Review B)

Directional Communication in Mobile Ad Hoc Networks - Grünewald, Matthias; Meyer auf der Heide, Friedhelm; Rührup, Stefan; Schindelhauer, Christian; Volbert, Klaus (New Trends in Parallel & Distributed Computing, 6th Int. Heinz Nixdorf Symposium)

Distributional data and grammatical structures: The case of so- called subject extraposition - Mindt, Ilka (Zeitschrift für Anglistik und Amerikanistik 54.2, Special issue on "The scope and Limits of Corpus Linguistics – Empiricism in the Description and Analysis of English)

Computing Clustering Coefficients in Data Streams - Sohler, Christian; Frahling, Gereon; Marchetti-Spaccamela, Alberto; Leonardi, Stefano; Buriol, Luciana (Proceedings of the European Conference on Complex Systems (ECCS'06))
We present random sampling algorithms that with probability at least 1 - δ compute a (1 ± ǫ)- approximation of the clustering coefficient, the transitiv ity coefficient, and of the number of bipartite cliques in a graph given as a stream of edges. Our methods can be extended to approximately count the number of occurences of fixed constant-size subgraphs. Our a lgorithms only require one pass over the input stream and their storage space depends only on structural parameters of the graphs, the approxi- mation guarantee, and the confidence probability. For examp le, the algorithms to compute the clustering and transitivity coefficient depend on that coefficient but n ot on the size of the graph. Since many large social networks have small clustering and transitivity coe fficient, our algorithms use space independent of the size of the input for these graphs. We implemented our algorithms and evaluated their performance on networks from different appli- cation domains. The sizes of the considered input graphs varied from about 8, 000 nodes and 40, 000 edges to about 135 million nodes and more than 1 billion edges. For both algorithms we run experiments with a sample set size varying from 100, 000 to 1, 000, 000 to evaluate running time and approximation guarantee. Our algorithms appear to be time efficient for the se sample sizes.

Counting Triangles in Data Streams - Sohler, Christian; Frahling, Gereon; Marchetti-Spaccamela, Alberto; Leonardi, Stefano; Buriol, Luciana

A Distributed O(1)-Approximation Algorithm for the Uniform Facility Location Problem - Sohler, Christian; Gehweiler, Joachim; Lammersen, Christiane (Proceeedings of 18th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this paper, we present a randomized constant factor approximation algorithm for the metric minimum facility location problem with uniform costs and demands in a distributed setting, in which every point can open a facility. In particular, our distributed algorithm uses three communication rounds with message sizes bounded to O(log n) bits where n is the number of points. We also extend our algorithm to constant powers of metric spaces, where we also obtain a randomized constant factor approximation algorithm.

Dimensionen der Politik: Aufklärung, Utopie, Demokratie. Festschrift für Richard Saage zum 65. Geburtstag

Power-Aware Collective Tree Exploration - Dynia, Miroslaw; Korzeniowski, Miroslaw; Schindelhauer, Christian (Architecture of Computing Systems - ARCS)

Average and Smoothed Complexity of Geometric Structures - Damerow, Valentina

A Web Computing Environment for Parallel Algorithms in Java - Bonorden, Olaf; Meyer auf der Heide, Friedhelm; Gehweiler, Joachim (Journal on Scalable Computing: Practice and Experience)
We present a web computing library (PUBWCL) in Java that allows to execute tightly coupled, massively parallel algorithms in the bulk-synchronous (BSP) style on PCs distributed over the internet whose owners are willing to donate their unused computation power. PUBWCL is realized as a peer-to-peer system and features migration and restoration of BSP processes executed on it. The use of Java guarantees a high level of security and makes PUBWCL platform- independent. In order to estimate the loss of efficiency inherent in such a Java-based system, we have compared it to our C-based PUB-Library. As the unused computation power of the participating PCs is unpredictable, we need novel strategies for load balancing that have no access to future changes of the computation power available for the application. We develop, analyze, and compare different load balancing strategies for PUBWCL. In order to handle the influence of the fluctuating available computation power, we classify the external work load. During our evaluation of the load balancing algorithms we simulated the external work load in order to have repeatable testing conditions. With the best performing load balancing strategy we could save 39% of the execution time on average and even up to 50% in particular cases, in our test environment.

Distributed Load Balancing in Heterogeneous Peer-to-Peer Networks for Web Computing Libraries - Gehweiler, Joachim; Schomaker, Gunnar (Proceeedings of 10th IEEE/ACM International Symposium on Distributed Simulation and Real Time Applications (DS-RT))
We present a novel architecture for distributed computing in a peer-to-peer network. In particular, we realize the Paderborn University BSP-based Web Computing Library (PUBWCL), which formerly used a centralized client-server architecture for scheduling and load balancing, as a pure peer-to-peer system. Using distributed heterogeneous hash tables (DHHT), our architecture features scheduling and load balancing of tightly coupled, massively parallel algorithms in the bulk-synchronous (BSP) style with a minimal number of migrations.

Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts

Shoah in der deutschsprachigen Literatur

Der Kult der Arbeit als Ausgangspunkt für das neue menschliche Gemeinwesen der Zukunft. Émile Zolas „Le Travail“: Ein Urbild des Städtebaus im 20. Jahrhundert - Seng, Eva- Maria (Dimensionen der Politik: Aufklärung, Utopie, Demokratie. Festschrift für Richard Saage zum 65. Geburtstag)

„Im Kopf die Toten verwesen nicht“. Werner Fritschs „Theater des Todes“ - Eke, Norbert Otto (Zeitschrift für deutsche Philologie 125, Sonderheft: Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts)

Das Gedächtnis der Literatur. Zur Einführung - Eke, Norbert Otto; Allkemper, Alo (Zeitschrift für deutsche Philologie 125, Sonderheft: Das Gedächtnis der Literatur. Konstitutionsformen des Vergangenen in der Literatur des 20. Jahrhunderts)

Thomas Brasch: Fliegen im Gesicht - Eke, Norbert Otto (Deutsche Kurzprosa der Gegenwart)

Herta Müller: Drückender Tango - Eke, Norbert Otto (Deutsche Kurzprosa der Gegenwart)

Konfigurationen der Shoah in der Literatur der DDR - Eke, Norbert Otto (Shoah in der deutschsprachigen Literatur)